IMPLEMENTASI KEBIJAKAN KESEHATAN REPRODUKSI DI INDONESIA: SEBELUM DAN SESUDAH REFORMASI - Zainal Fatoni; Yuly Astuti; Sari Seftiani; Augustina Situmorang; Widayatun NFN; Sri Sunarti Purwaningsih (Research Centre for Population, Indonesian Institute of Sciences, 2015)
Policy on reproductive health is one of the essential determinant to address the goals of population and health development in Indonesia. Maternal Mortality Ratio (MMR), teenage marriage, and Total Fertility Rate (TFR) are among the indicators that show the important role of reproductive health policy. This article discusses the progress of reproductive health policy implementation in Indonesia and its implication to early marriage, TFR, and MMR. Data used in this paper are mainly derived through desk studies from previous research conducted by the Research Center for Population – Indonesian Institute of Sciences. The studies consist of reproductive health policy and regional autonomy (2000-2005), BKKBN’s decentralization (2005), HIV/AIDS in border areas (2006-2009), and the implementation of integrated reproductive health services in primary health care (2007). Desk reviews are also used to analyze current studies from LIPI that are related to these issues. LIPI’s [AD1] studies showed that there is a gap between the implementation of reproductive health policy at the global and national level with the district level. The implementation of reproductive health services are not yet integrated as it is less popular than adolescent reproductive health policy. Policy priorities for relevant stakeholders have not been implemented synergically. The implementation of decentralization policy in early 2000’s created various commitments from the local government in prioritizing reproductive health programs. BKKBN’s decentralization, for example, has affected not only the structure of its institution at district level, but also the function of the family planning facilitator at village level. Meanwhile, pilot project implementation on the integrated essential reproductive health services in primary health cares that has significant contribution also faced uncertainty in terms of its continuation. Hence, this article suggests the importance of synergizing reproductive health policy at the global, national, and district level to meet the appropriate situation and needs at the local context. Otherwise, teenage marriage, TFR, and MMR as well as other population issues will be further overlooked.